Costs of examinations performed in a hospital laboratory in Chile - Germán Lobos Andrade; Carolina Salas Palma
ABSTRACT Objective: To determine the total average costs related to laboratory examinations performed in a hospital laboratory in Chile. Method: Retrospective study with data from July 2014 to June 2015. 92 examinations classified in ten groups were selected according to the analysis methodology. The costs were estimated as the sum of direct and indirect laboratory costs and indirect institutional factors. Results: The average values obtained for the costs according to examination group (in USD) were: 1.79 (clinical chemistry), 10.21 (immunoassay techniques), 13.27 (coagulation), 26.06 (high-performance liquid chromatography), 21.2 (immunological), 3.85 (gases and electrolytes), 156.48 (cytogenetic), 1.38 (urine), 4.02 (automated hematological), 4.93 (manual hematological). Conclusion: The value, or service fee, returned to public institutions who perform laboratory services does not adequately reflect the true total average production costs of examinations.